2021
DOI: 10.1155/2021/9959954
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Deep Reinforcement Learning in E-Learning and Distance Learning: Remote Practical Work

Abstract: The world has seen major developments in the field of e-learning and distance learning, especially during the COVID-19 crisis, which revealed the importance of these two types of education and the fruitful benefits they have offered in a group of countries, especially those that have excellent infrastructure. At the Faculty of Sciences Semlalia, Cadi Ayyad University Marrakech, Morocco, we have created a simple electronic platform for remote practical work (RPW), and its results have been good in terms of stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 19 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Aside from research of RL in robotics and game theory, Abedali El Gourari et al also delved into the implementation of Deep RL in e-learning and distance learning [26]. They adopted a framework for promoting learning and focused on the implementation of Deep Q-Networks to train the agent or a virtual teacher to do Remote Practical Work (RPW) in a short period.…”
Section: Contributions and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from research of RL in robotics and game theory, Abedali El Gourari et al also delved into the implementation of Deep RL in e-learning and distance learning [26]. They adopted a framework for promoting learning and focused on the implementation of Deep Q-Networks to train the agent or a virtual teacher to do Remote Practical Work (RPW) in a short period.…”
Section: Contributions and Related Workmentioning
confidence: 99%
“…Agrebi et. al [67] obtained 48% accuracy with DQN and lastly Shahbazi and Byun [68] used Double Deep Q-Network which produced 21.46% accuracy [26]. In Robotics, Alvaro et al implemented Meta RL for the optimal design of legged robots.…”
Section: Risk Across Fixed Policy Rollouts (Rf)mentioning
confidence: 99%
“…The following problems have been studied in selected PRISMA research papers: Higher education quality assurance ( Alakbarov 2021 ; Allayarova 2019 ; Asare et al 2021 ); Knowledge-based recommender system ( Barabash et al 2021 ; Barón et al 2015 ; Bin-Noor et al 2021 ; Brunello and Wruuck 2021 ); E-learning and distance learning ( Bukralia et al 2015 ; Burman et al 2021 ; Casselman 2021 ; Chahal et al 2020 ); Inter-professional education ( Cheng 2017 ); Network course recommendation system ( Cinquin et al 2019 ; Dhar and Jodder 2020 ; Dolgikh 2021 ; Ehimwenma and Krishnamoorthy 2021 ); Modern information communication technologies in the higher education sector ( El Gourari et al 2021 ; Elahi et al 2022 ; Ellyatt 2021 ; Elumalai et al 2019 ); Transformation of education during the COVID-19 pandemic ( Erridge 2006 ; Ezz and Elshenawy 2020 ; Fedushko and Ustyianovych 2020 ); Digitalization in higher education ( Gao et al 2021 ; Garay-Jiménez et al 2021 ; Gil et al 2019 ); Personalized recommendation system for learning resources ( Habib et al 2021 ; Ibrahim et al 2019 ; Karan and Asgari 2021 ; Khan and Ramzan 2018 ; Khosravi et al 2021 ); Artificial intelligence techniques for education tasks solving ( Kim Rosemary et al 2014 ; ...…”
Section: Literature Reviewmentioning
confidence: 99%
“…Modern information communication technologies in the higher education sector ( El Gourari et al 2021 ; Elahi et al 2022 ; Ellyatt 2021 ; Elumalai et al 2019 );…”
Section: Literature Reviewmentioning
confidence: 99%
“…We have implemented a reinforcement learning-based model inspired by Boloka et al [76], who suggested an environment-independent deep reinforcement learning (DRL) framework for transferring information from a model-based teacher to a task-specific modelfree learner in order to avoid executing a randomly initialized policy in the early stages of learning. DRL is a subgenre of reinforcement learning that employs deep neural networks to allow DRL algorithms to function in continuous and high-dimensional settings [77] and is suitable to monitor the learner's progress and adjust the training curve [78].…”
Section: Model Of Knowledge Transfermentioning
confidence: 99%